2021
DOI: 10.1161/strokeaha.120.033667
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Carotid Revascularization in the Treatment of Restenosis After Prior Carotid Endarterectomy

Abstract: Background and Purpose: Restenosis after carotid endarterectomy (CEA) is associated with an increased risk of ipsilateral stroke. The optimal procedural modality for this indication has yet to be determined. Here, we evaluate the in-hospital outcomes of transcarotid artery revascularization (TCAR), redo-CEA, and transfemoral carotid artery stenting (TFCAS) in a large contemporary cohort of patients who underwent treatment for restenosis after CEA. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Analysis of 4425 patients with restenosis after CEA in VQI demonstrated that TCAR was associated with lower odds of in-hospital stroke/death (OR ¼ 0.41 [95% CI: 0.24-0.70]; P ¼ .021), and MI (OR ¼ 0.32 [95% CI: 0.14-0.73]; P ¼ .007), when compared with redo-CEA. TCAR was also associated with lower odds of stroke/TIA (OR ¼ 0.37 [95% CI: 0.18-0.74]; P ¼ .005) when compared with TFCAS [96]. In another national study from our team, CEA and CAS following prior CAS were compared.…”
Section: Restenosis Following Carotid Revascularizationmentioning
confidence: 99%
“…Analysis of 4425 patients with restenosis after CEA in VQI demonstrated that TCAR was associated with lower odds of in-hospital stroke/death (OR ¼ 0.41 [95% CI: 0.24-0.70]; P ¼ .021), and MI (OR ¼ 0.32 [95% CI: 0.14-0.73]; P ¼ .007), when compared with redo-CEA. TCAR was also associated with lower odds of stroke/TIA (OR ¼ 0.37 [95% CI: 0.18-0.74]; P ¼ .005) when compared with TFCAS [96]. In another national study from our team, CEA and CAS following prior CAS were compared.…”
Section: Restenosis Following Carotid Revascularizationmentioning
confidence: 99%
“…TCAR is associated with a significantly lower risk of in-hospital stroke/death, stroke, stroke/TIA, MI, and stroke/death/MI compared to redo-CEA. In addition, TCAR carries a lower risk of in-hospital stroke/TIA compared to TF-CAS [ 61 ]. Risk factors, such as previous stroke, ischemic heart disease (IHD), and the degree of stenosis, have been found to be associated with postoperative complications.…”
Section: Reviewmentioning
confidence: 99%
“…21 It has been shown in numerous clinical trials that TCA has a lower stroke rate. [22][23][24][25] Despite this, the benefits and risks of TCA compared with TFA are unclear, and there is no guideline that assists clinicians in making the right choice. The purpose of this study is to compare the safety and efficacy of TCA versus TFA for cerebrovascular interventions.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…As compared with TFA, TCA eliminates the need to traverse the aortic arch, reduces the production of debris and the risk of atheroembolisation, and takes a shorter procedure period 21. It has been shown in numerous clinical trials that TCA has a lower stroke rate 22–25. Despite this, the benefits and risks of TCA compared with TFA are unclear, and there is no guideline that assists clinicians in making the right choice.…”
Section: Introductionmentioning
confidence: 99%